Karakteristik dan Keindahan Syair Barat Ibnu Hani Al-Andalusi: Analisis Syair Masa Daulah Abbasyiah - Ledianto, Fajar; Nuruddin, Ahmad; Rufaiqoh, Elok; A’laa, Achmad Amry Zumaro (Dzil Majaz: Journal of Arabic Literature, 2024)
This research aims to analyze the characteristics and beauty of Ibn Hani Al-Andalusi's western poetry during the Abbasid period. This research is library research with qualitative descriptive research methods. The data and data sources are words or sentences included in the poetry of Ibnu Hani Al-Andalusi. This research will discuss in detail the characteristics and beauty of Ibnu Hani Al-Andalusi's poetry. The results of this research show that Ibnu Hani Al-Andalusi was a poet who wrote a lot about praise poetry (al-Madh) which was mainly used for the caliph Mu'iz Lidinillah, however, the poetry still contains sub-texts. sub-themes such as lamentation (Al-Ritsa'), reproach/insult (Al-Hija'), seduction (Al-Ghazal), and description (Al-Washf). The forms of beauty of poetry that will be studied are in terms of theme, emotion ('athifah), imagination (khayāl), language style and poetry literature which includes the science of balaghah. From these studies, the beauty of the language of Ibn Hani Al-Andalusi's poetry will be seen, so that we can find out how beautiful the western poetry works that were famous during the Abbasid era were